2018
DOI: 10.1177/1468794118787712
|View full text |Cite
|
Sign up to set email alerts
|

Militant ethnography and autonomous politics in Latin America

Abstract: This article discusses the relevance of militant ethnography as a collaborative and politically engaged form of knowledge production for the study of Latin American social movements. Drawing on my militant ethnographic research with four autonomous groups from Chile and Mexico, the article presents a reflective account of my experience as a militant researcher throughout the different stages of the inquiry. More specifically, I describe the ethical and methodological procedures carried out in the field and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…This notion of extractivism in research also links to how ethnography might be undertaken among Latin American resistance politics. Valenzuela-Fuentes (2019) reflects on her unease at carrying out ethnographic fieldwork among Chilean activists while taking her data back to a European university for production into a PhD submission. In response to this, a methodological switch takes place where the researcher prioritizes an on-going process of collaboration and solidarity over the abstraction of research data.…”
Section: Militant Design Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This notion of extractivism in research also links to how ethnography might be undertaken among Latin American resistance politics. Valenzuela-Fuentes (2019) reflects on her unease at carrying out ethnographic fieldwork among Chilean activists while taking her data back to a European university for production into a PhD submission. In response to this, a methodological switch takes place where the researcher prioritizes an on-going process of collaboration and solidarity over the abstraction of research data.…”
Section: Militant Design Researchmentioning
confidence: 99%
“…In practical terms, this involves adopting an immersive approach that ‘rejects detachment between thinking and doing politics and the understanding of researchers as experts who will explain the movements [we work with] through disembodied knowledge’ (Valenzuela-Fuentes, 2019: 723). This means giving precedence to political and everyday actions that address the concrete collective needs of the people we work with, rather than academic demands that commonly involve long production circles, addressing a particular reduced audience.…”
Section: Committing To Tensionsmentioning
confidence: 99%
“…In the anti-oppressive research tradition, researchers are expected to minimize hierarchical structures and practices as they work towards horizontality (Valenzuela-Fuentes, 2019). We found that Interpretive Description was helpful in this regard as it has focused since its inception on shifting power differentials within both research process and product.…”
Section: Using Power and Privilege Wiselymentioning
confidence: 99%
“…Starodub, 2019), these scholar-activists mainly employed a participant observation or (auto)ethnographic method of militant research (see Apoifis, 2016Apoifis, , 2017U. Gordon, 2012;Graeber, 2009;Halvorsen, 2015;Juris, 2007;Russell, 2015;Valenzuela-Fuentes, 2018). Dialoguing with their writing allowed me to pre-empt many of the difficulties facing this method in Calais.…”
Section: Ethics Of Militant Research and Producing Knowledge Of Migrationmentioning
confidence: 99%